New Frontiers or Old Certainties: The pre-service teacher internship - Broadley, Tania; Sharplin, E.; Ledger, S. (Oxford Global Press, 2013)
Teacher education in Australia has a rich history of evolution from apprenticeships to university education. In this chapter the teacher education internship is examined. More specifically, the chapter outlines the Western Australian Combined Universities Training School (WACUTS) project, with its focus on reducing the gap between theory and practice through a collaborative and reflective approach. The successes and challenges faced in the first six months of implementation are presented.